ANALISYS OF THE EFFECT OF CORPORATE CREDIBILITY, ENDORSER IMAGE, AND AD APPEAL TOWARD BUYING INTEREST - Andi Tri Haryono (Universitas Pandanaran, 2015)
The purpose of this study was to develop a theoretical model of the research gap on endorserimage effects, adding intervening variables top of mind, for consumers to buy. The research object is selected in this study is a product of cellular card